Efektivitas penagihan pajak dengan surat teguran dan surat paksa terhadap penerimaan pajak pada kantor pelayanan pajak (kpp) pratama di balikpapan - Putri Kurniasari Kurniasari; Suharyono Suharyono; Agus Iwan Kesuma (AKUNTABEL, 2016)
The purpose of this research is to know the effectiveness of the tax collection by the warning letter and distress warrant in KPP Pratama Balikpapan in order to increase tax revenue. And to know the contribution of the tax collection  by the warning letter and distress warrant to the disbursement of tax arrears at KPP Pratama Balikpapan. The methode used in this research are descriptive analysis, effectiveness ratio and the ratio of contributions to the data collection techniques such as observation, interviews, and documentation. This research found that the collection tax by the warning letter and distress warrant in KPP Pratama Balikpapan could be classified as enough effective. And to the contribution to the disbursement of tax arrears is still lacking. so much needed improvement in the tax collectionKeyword: Effectiveness, Tax billing, Warning letter, Distress warrant, and Tax Revenue.